Duck Tembusu virus in North Vietnam: epidemiological and genetic analysis reveals novel virus strains - Dong, Hieu Van; Tran, Giang Thi Huong; Vu, Tra Thi Thu; Le, Ngan Hong Thi; Nguyen, Yen Thi Hoang; Rapichai, Witsanu; Rattanasrisomporn, Amonpun; Boonkaewwan, Chaiwat; Bui, Dao Anh Tran; Rattanasrisomporn, Jatuporn (Frontiers in Veterinary Science, 2024)
Tembusu virus (TMUV) is an important infectious disease, causing economic losses in duck production. Since the first report of TMUV infection in Vietnam in 2020, the disease has persisted and affected poultry production in the country. This study conducted epidemiological and genetic characterization of the viral strains circulating in north Vietnam based on 130 pooled tissue samples collected in six provinces/cities during 2021. The TMUV genome was examined using conventional PCR. The results indicated that 21 (16.15%) samples and 9 (23.68%) farms were positive for the viral genome. The positive rate was 59.26% for ducks at ages 2–4 weeks, which was significantly higher than for ducks at ages >4 weeks and < 2 weeks. Genetic analysis of the partial envelope gene (891 bp) sequences indicated that the five Vietnamese TMUVs shared 99.55–100% nucleotide identity, while the rates were in the range 99.59–100% based on the pre-membrane gene sequences (498 bp). The five Vietnamese TMUV strains obtained formed a novel single subcluster. These strains were closely related to Chinese strains and differed from the vaccine strain, suggesting that Vietnamese TMUV strains were field viruses. It needs to be further studied on vaccine development to prevent effects of TMUV infection on poultry production across Vietnam.